Water-based thermal insulation material containing rare earth elements
By using water-based thermal insulation materials containing rare earth elements in crude oil storage tanks, the problems of poor thermal insulation reflection effect, high construction cost, poor water resistance and poor corrosion resistance are solved, and efficient and environmentally friendly Insulation effect.
Patent Information
- Application Number
- CN202411705870.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-07
AI Technical Summary
When existing thermal insulation coatings are used in crude oil storage tanks, there are problems such as unsatisfactory thermal insulation reflection effect, high construction cost, poor water resistance and poor corrosion resistance.
Using aqueous thermal insulation materials containing rare earth elements, the components of modified silicon acrylic emulsion, modified hollow glass microbeads, rare earth nano-insulators and nano-TiO2 modified aerogel dispersion are used. Form a coating with excellent adhesion, thermal insulation effect, corrosion resistance and water resistance.
It achieves extremely low thermal conductivity and excellent thermal insulation temperature difference, has good corrosion resistance, water resistance and aging resistance, light coating quality and controllable thickness, has the advantages of energy-saving and environmentally friendly performance, and is simple in construction technology and production The process is relatively simple, with low energy consumption and low emissions.
Smart Images

Figure BDA0005154496810000101
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating technology, and in particular to a water-based thermal insulation material containing rare earth elements. Background Art
[0002] Crude oil storage tanks are safer, more economical and more reasonable when storing oil products. This is a hot topic for scholars at home and abroad. During long-term static storage or transportation, crude oil will solidify due to low temperature. Some heating measures are often used to heat the tank to keep the oil temperature above its solidification point. In the context of a resource-saving society, how to prevent heat from being lost during transmission and improve energy utilization is a great need of society. Therefore, thermal insulation coatings came into being.
[0003] Thermal insulation coatings, due to their light weight, good waterproofness and toughness, can integrate waterproofing, thermal insulation, exterior protection and other functions, and can simplify the construction process. With the rapid development of the oil production and petrochemical industries, they will be able to save a lot of energy and have good development prospects.
[0004] At present, the most widely used insulation measures in crude oil storage tanks are: installing rock wool insulation boards on the tank walls or applying thermal insulation coatings. Among them, rock wool boards have a low thermal conductivity and excellent thermal insulation performance, but they require very high construction and installation technology, and they also face many problems such as damage and aging during the application process. Compared with the method of installing rock wool insulation boards, thermal insulation coatings have the advantages of multi-pass molding, simple construction, and no joints; in addition, thermal insulation coatings used in crude oil storage tanks, while ensuring their excellent thermal insulation effects, also need to have excellent corrosion resistance, excellent water resistance, light coatings, and controllable coatings.
[0005] Although there are many studies on thermal insulation coatings for storage tanks in China, the thermal insulation effects vary. Some thermal insulation coatings have complex preparation methods and unsatisfactory thermal insulation reflection effects. Some thermal insulation coatings require thicker coatings to achieve better thermal insulation effects, but the construction effect is poor and the cost is high. Some thermal insulation coatings have good thermal insulation effects, but poor water resistance, resulting in poor thermal insulation effects after absorbing water. Some thermal insulation coatings have poor corrosion resistance. Summary of the invention
[0006] The purpose of the present application is to provide a water-based thermal insulation material containing rare earth elements in response to the deficiencies of the current technology. The water-based thermal insulation material containing rare earth elements prepared in the present application has excellent adhesion, good thermal insulation effect, extremely low thermal conductivity and excellent thermal insulation temperature difference; it has excellent corrosion resistance and water resistance, and good aging resistance; the coating is light in weight, the thickness of the formed coating is controllable, and the non-volatile matter content is high, and it has the advantages of energy saving and good environmental protection performance; the construction process is relatively simple, and it can be applied manually or by roller coating, spraying, etc.; and the production process is relatively simple, and it has the advantages of low energy consumption and low emissions.
[0007] The present application provides a water-based thermal insulation material containing rare earth elements, which adopts the following technical solution: A water-based thermal insulation material containing rare earth elements comprises the following raw materials by mass: 50-55 parts of water-based hollow elastic rubber microsphere modified silicone acrylic emulsion, 12-15 parts of modified hollow glass microspheres, 7-9 parts of rare earth nano thermal insulation agent, 12-14 parts of nano TiO2 modified aerogel dispersion, 6-8 parts of kaolin, 0.5-0.8 parts of thickener, 0.5-0.7 parts of dispersant, 1.5-2 parts of film former, 1.4-1.6 parts of defoamer and 10-12 parts of deionized water, wherein the rare earth nano thermal insulation agent is an aqueous dispersion slurry of cerium-based rare earth oxides.
[0008] By adopting the above technical scheme, water-based hollow elastic rubber microspheres modified silicone acrylic emulsion: as a base material, it provides good adhesion and thermal insulation effects. Its hollow structure helps to reduce thermal conductivity and improve the thermal insulation performance of the coating. At the same time, it has good solubility with other components such as rare earth nano thermal insulation agents and modified hollow glass microspheres, which is conducive to the formation of a stable coating system. Modified hollow glass microspheres: improve surface properties through chemical reactions so that they can better combine and disperse with the emulsion base material. Its role in water-based thermal insulation materials is to reduce thermal conductivity, improve the thermal insulation performance of the coating, and reduce heat transfer. It interacts with nano-TiO2 modified aerogel to enhance the stability of the coating system, and has common anti-corrosion and water resistance, and good aging resistance. Rare earth nano thermal insulation agent (aqueous dispersion slurry of cerium-based rare earth oxides): has good transparency and does not affect the light transmittance and color of the coating. Ce of cerium-based oxides 3+ and Ce 4+ The reversible transformation between oxidation states, the resulting electronic resonance and energy level transition, greatly improve the thermal insulation performance of the coating. 3+ and Ce 4+The reversible transformation process between oxidation states has a certain effect on the absorption of ultraviolet rays, so it has a significant effect on the anti-ultraviolet aging performance of the coating. Nano-TiO2 modified aerogel dispersion: Nano-TiO2 and γ-aminopropyltriethoxysilane are used to modify the surface structure and state of silica gel, improve the dispersibility of silica gel in the emulsion, and then improve the thermal insulation performance of the coating. At the same time, through nano-TiO2 modification, the aging resistance of water-based thermal insulation materials is improved. Kaolin: As a filler, it increases the volume and weight of the coating and improves the hiding power and adhesion of the coating. At the same time, kaolin has good weather resistance and chemical stability, which helps to improve the durability of the coating. Thickeners, dispersants, film formers, defoamers and other additives: used to adjust the viscosity, fluidity, film forming properties and other properties of the coating, so that the coating has better construction performance and application effect. In summary, the various components in the present application play different roles in the water-based thermal insulation material, and through synergistic effects, achieve excellent thermal insulation effects, corrosion resistance, water resistance and aging resistance.
[0009] Preferably, the method for preparing the aqueous hollow elastic rubber microsphere modified silicone acrylic emulsion comprises the following steps: S21, according to the mass fraction, add 4 parts of sodium dodecyl phosphate to 100 parts of deionized water, stir evenly, add 12 parts of hollow elastic nano rubber microspheres, stir at a speed of 500 r / min for 30 min, and obtain a dispersion; S22, adding 30 parts of butyl methacrylate, 13 parts of hexamethylcyclotetrasiloxane, 3 parts of potassium persulfate and 15 parts of 25% ammonia water to the dispersion according to their weight parts, introducing nitrogen gas and stirring for 20 minutes, then heating to 83° C. and keeping the temperature for 40 minutes to obtain a reaction solution; S23. Add 25 parts of ethyl acrylate, 40 parts of vinyltrimethoxysilane and 10 parts of 30% potassium persulfate aqueous solution into the reaction solution according to their mass fractions. After reacting for 2 hours, cool to room temperature to obtain an aqueous hollow elastic rubber microsphere modified silicone acrylic emulsion.
[0010] By adopting the above technical scheme, the water-based hollow elastic rubber microsphere modified silicone acrylic emulsion of the present application plays a key role in the preparation of water-based thermal insulation materials containing rare earth elements. The following are its roles and synergistic effects in the material: 1. Enhance system stability: The water-based hollow elastic rubber microsphere modified silicone acrylic emulsion prepared by copolymerization allows the hollow elastic nano rubber microspheres to be fully combined and dispersed with the matrix resin, thereby enhancing the stability of the entire coating system. This stability helps to improve the properties of the coating, such as adhesion, durability and aging resistance. 2. Improve thermal insulation effect: The water-based hollow elastic rubber microspheres have good thermal insulation properties because their internal structure can prevent heat transfer. When these microspheres are added to the coating system, they can significantly reduce the thermal conductivity of the material, thereby improving the thermal insulation effect of the entire coating. 3. Lightweight and controllable thickness: Since the water-based hollow elastic rubber microspheres are light in weight, the coating made is also relatively light. In addition, since the size and shape of these microspheres can be controlled, the thickness and density of the coating can be controlled by adjusting their addition amount. 4. Good environmental performance: Water-based hollow elastic rubber microspheres modified silicone acrylic emulsion is an environmentally friendly product because it does not contain organic solvents and other harmful substances. This makes it have less impact on the environment during production and use. 5. Simple construction process: Since the water-based hollow elastic rubber microspheres modified silicone acrylic emulsion has good fluidity and adhesion, it can be constructed by manual coating, roller coating or spraying. This makes the construction process relatively simple and saves manpower and time costs. In summary, the water-based hollow elastic rubber microspheres modified silicone acrylic emulsion plays a role and synergistic effect in the water-based thermal insulation material containing rare earth elements in this application, such as enhancing system stability, improving thermal insulation effect, light weight and controllable thickness, good environmental protection performance and simple construction process.
[0011] Preferably, the preparation method of the hollow elastic nano rubber microspheres is as follows: 75g of hollow glass microspheres with a particle size of 20 microns, 380g of vulcanized rubber elastic powder with a particle size of 15 microns, 1.2g of dodecyldimethylbenzyl ammonium chloride, and 0.8g of γ-aminopropyltriethoxysilane are heated under reflux at 150°C for 20min in 150g of ethylene glycol butyl ether solvent, cooled and filtered, and the filtrate is placed in an oven at 60°C and baked for 24h to obtain hollow elastic nano rubber microspheres.
[0012] Preferably, the method for preparing the modified hollow glass microspheres comprises the following steps: S41, soaking 200 g of hollow glass microspheres with a particle size of 20 μm in 2 L of 15% vinyltrimethoxysilane modified treatment solution and stirring for 30 minutes, filtering and drying to obtain an intermediate material; S42, add 100g of the intermediate material and 500mL of xylene into the reactor and mix evenly, then add 290g of phenylindanedione and 125g of methyl 4-benzoylbutyrate, then add 3g of sodium methoxide under constant stirring and react at 40°C for 7h, and after reduced pressure distillation, washing and drying, the modified hollow glass microspheres are obtained.
[0013] By adopting the above technical scheme, the preparation method of modified hollow glass microspheres includes the following steps: immersing 200g of hollow glass microspheres with a particle size of 20 microns in 2L of 15% mass concentration vinyltrimethoxysilane modified treatment liquid and stirring for 30 minutes, filtering and drying to obtain an intermediate material. The purpose of this step is to improve the surface properties of hollow glass microspheres through chemical reactions so that they can be better combined with the emulsion base material and dispersed. Add 100g of intermediate material and 500mL of xylene to the reactor and mix evenly, then add 290g of phenylindanedione and 125g of 4-benzoylbutyric acid methyl ester, then add 3g of sodium methoxide under continuous stirring and react at 40°C for 7h, and after reduced pressure distillation, washing and drying, the modified hollow glass microspheres are obtained. The purpose of this step is to make the hollow glass microspheres have better modification functions through further chemical reactions, thereby improving their performance in water-based thermal insulation materials. The role and synergistic effect of modified hollow glass microspheres are mainly reflected in the following aspects: Reduce thermal conductivity: The role of modified hollow glass microspheres in water-based thermal insulation materials is to reduce thermal conductivity, improve the thermal insulation performance of the coating, and reduce heat transfer. Enhance the stability of the coating system: Interacting with nano-TiO2 modified aerogel, the modified hollow glass microspheres can enhance the stability of the coating system, and have good anti-corrosion and water resistance, and aging resistance. Improve the thermal insulation performance of the coating: The modified hollow glass microspheres improve the thermal insulation performance of the coating and reduce heat transfer by reducing thermal conductivity. Promoting the hollow elastic nano rubber microspheres to more fully exert the effect of thermal insulation: adding hollow elastic nano rubber microspheres to the reaction system of water-based hollow elastic rubber microspheres modified silicone acrylic emulsion, copolymerization reaction to prepare water-based hollow elastic rubber microspheres modified silicone acrylic emulsion with hollow elastic nano rubber microspheres as cores and silicone acrylic resin as shells, so that the hollow elastic nano rubber microspheres and the matrix resin are fully combined and dispersed, the stability of the system is enhanced, and the hollow elastic nano rubber microspheres are promoted to more fully exert the effect of thermal insulation.
[0014] Preferably, the method for preparing the nano-TiO2 modified aerogel dispersion comprises the following steps: S51, according to the mass parts, add 100 parts of TiO2 powder with a particle size of 20 nanometers and 15 parts of Tego760W, a wetting and dispersing agent, to 50 parts of deionized water, and disperse for 5 minutes at a dispersion speed of 400 r / min to obtain a solution A; S52, according to the mass fractions, add 15 parts of fumed silica gel and 2 parts of hydroxyethyl cellulose to 50 parts of deionized water, then add 0.5 parts of γ-aminopropyltriethoxysilane, and disperse for 10 minutes at a dispersion speed of 600 r / min to obtain a solution B; S53, adding solution B into solution A, dispersing for 20 minutes at a dispersing speed of 800 r / min, to obtain a nano-TiO2 modified fumed silica gel dispersion.
[0015] By adopting the above technical solution, the prepared nano-TiO2 modified aerogel dispersion can improve the thermal insulation performance of the coating and reduce the heat transfer. The surface structure and state of silica gel are modified by nano-TiO2 and γ-aminopropyltriethoxysilane, which improves the dispersibility of silica gel in the emulsion, thereby improving the thermal insulation performance of the coating. Nano-TiO2 modified aerogel dispersion can improve the aging resistance of water-based thermal insulation materials. Since nano-TiO2 has good transparency, it does not affect the light transmittance and color of the coating, and Ce 3+ and Ce 4+ The reversible transformation process between oxidation states has a certain effect on the absorption of ultraviolet rays, and therefore significantly improves the anti-ultraviolet aging performance of the coating. Nano-TiO2 modified aerogel dispersion can enhance the stability of the coating system. Through interaction with hollow elastic nano rubber microspheres, nano-TiO2 modified aerogel can better play the role of heat insulation. At the same time, the coating is light in weight, the thickness of the formed coating is controllable, and the non-volatile content is high, which has the advantages of energy saving and good environmental protection performance.
[0016] Preferably, the thickener is hydroxypropyl methylcellulose.
[0017] Preferably, the dispersant is prepared by mixing BYK-190, sodium dodecyl phosphate and sodium dodecylbenzene sulfonate in a mass ratio of 3:4:3.
[0018] By adopting the above technical solution, the role of the dispersant is to help the solid particles in the coating (such as modified hollow glass microspheres, rare earth nano thermal insulation agents, etc.) to be evenly dispersed in the liquid medium (aqueous emulsion), prevent the particles from aggregating and settling, and thus ensure the uniformity and stability of the coating. BYK-190 is a high molecular weight wetting and dispersing additive that can improve the dispersibility of pigments and fillers in the coating, reduce pigment flocculation, and improve the stability and gloss of the coating. Sodium dodecyl phosphate and sodium dodecylbenzene sulfonate are anionic surfactants that make solid particles more easily wetted and dispersed by liquids by reducing the surface tension of the liquid. The synergistic effect of these three dispersants is that different dispersants have different molecular structures and properties, and their combination can provide a more comprehensive dispersion effect and adapt to different types of solid particles. There may be a positive synergistic effect between some dispersants, that is, their combination is better than when used alone. This may be because their interaction at the interface enhances the stable dispersion of solid particles. Through reasonable proportioning, this mixed dispersant can be applied to a variety of different coating systems to improve its versatility. In summary, this specific dispersant blend is carefully designed to optimize the preparation process and final performance of water-based thermal insulation materials. It ensures good dispersion of the various components in the coating, thereby improving the overall performance of the coating, including adhesion, thermal insulation effect, water resistance, corrosion resistance and aging resistance.
[0019] Preferably, the film-forming agent is propylene glycol methyl ether acetate.
[0020] Preferably, the defoaming agent is dimethyl silicone oil.
[0021] Preferably, the method for preparing the water-based thermal insulation material containing rare earth elements comprises the following steps: S101, respectively adding water-based hollow elastic rubber microsphere modified silicone acrylic emulsion, modified hollow glass microspheres, rare earth nano thermal insulation agent, nano-TiO2 modified aerogel dispersion, kaolin, and deionized water into a reactor according to their mass fractions, and stirring at a speed of 300 r / min for 40 min to obtain a mixed solution; S102. Add thickener, dispersant, film-forming agent and defoaming agent to the mixed solution according to their mass fractions, stir at a speed of 1200 r / min for 30 min, and obtain a water-based thermal insulation material containing rare earth elements.
[0022] In summary, the beneficial technical effects of this application are: 1. Excellent adhesion and thermal insulation effect: The water-based thermal insulation material containing rare earth elements prepared by using water-based hollow elastic rubber microspheres modified silicone acrylic emulsion, modified hollow glass microspheres, rare earth nano thermal insulation agent, nano TiO2 modified aerogel dispersion and other raw materials has excellent adhesion and thermal insulation effect. The combination of these raw materials enables the coating to form a firm coating on the surface of various substrates, and can effectively isolate the transfer of heat to achieve a good thermal insulation effect.
[0023] 2. Extremely low thermal conductivity and excellent thermal insulation temperature difference: Due to the use of low thermal conductivity materials such as modified hollow glass microspheres and nano-TiO2 modified aerogel dispersions, as well as rare earth nano thermal insulation agents of cerium-based rare earth oxides, the prepared water-based thermal insulation material has extremely low thermal conductivity and excellent thermal insulation temperature difference. This means that at the same thickness, the material can better prevent the transfer of heat, thereby improving the thermal insulation effect.
[0024] 3. Good anti-corrosion and water resistance: By using raw materials such as kaolin, thickeners, dispersants, and special production processes, the prepared water-based thermal insulation materials have good anti-corrosion and water resistance. This allows the material to maintain its performance stable even in a humid environment and is not easily affected by corrosion and moisture.
[0025] 4. Good aging resistance: Due to the use of materials with good aging resistance such as nano-TiO2 modified aerogel dispersion and rare earth nano thermal insulation agents of cerium rare earth oxides, the prepared water-based thermal insulation material has good aging resistance. This means that the material can resist the erosion of external factors such as ultraviolet rays and oxygen during use, extending its service life.
[0026] 5. The coating is light, the thickness of the coating can be controlled, and the non-volatile content is high: by using light raw materials such as water-based hollow elastic rubber microspheres modified silicone acrylic emulsion, and a special production process, the prepared water-based thermal insulation material has the characteristics of light weight. At the same time, due to the good fluidity of the coating, the thickness of the coating can be easily controlled to meet the needs of different occasions. In addition, the non-volatile content of the material is high, which is beneficial to environmental protection and energy saving.
[0027] 6. The construction process is relatively simple: Since water-based thermal insulation materials have good fluidity and adhesion, they can be constructed by manual application, roller coating, spraying and other methods, which is easy to operate. At the same time, due to the fast drying speed of the coating, the construction period can be shortened and the construction efficiency can be improved.
[0028] 7. The production process is relatively simple, with low energy consumption and low emissions: The production process of this application is relatively simple, does not require complex equipment and conditions, and is conducive to reducing production costs. At the same time, due to the use of an aqueous system, the use of organic solvents is reduced, energy consumption and emissions are reduced, and it is beneficial to environmental protection. DETAILED DESCRIPTION
[0029] The embodiments of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, the rare earth nano thermal insulation agent is purchased from the Baotou Rare Earth Research Institute, model: WLS-020, and BYK-190 is the German BYK-190 wetting and dispersing agent.
[0030] In the following examples and preparation examples, 1 part means 100 g.
[0031] Preparation Example 1 Preparation of water-based hollow elastic rubber microsphere modified silicone acrylic emulsion The preparation method of water-based hollow elastic rubber microsphere modified silicone acrylic emulsion comprises the following steps: S21, according to the mass fraction, add 4 parts of sodium dodecyl phosphate to 100 parts of deionized water, stir evenly, add 12 parts of hollow elastic nano rubber microspheres, stir at a speed of 500 r / min for 30 min, and obtain a dispersion; S22, adding 30 parts of butyl methacrylate, 13 parts of hexamethylcyclotetrasiloxane, 3 parts of potassium persulfate and 15 parts of 25% ammonia water to the dispersion according to their weight parts, introducing nitrogen gas and stirring for 20 minutes, then heating to 83° C. and keeping the temperature for 40 minutes to obtain a reaction solution; S23, according to the mass fractions, 25 parts of ethyl acrylate, 40 parts of vinyl trimethoxysilane and 10 parts of potassium persulfate aqueous solution with a mass concentration of 30% are added dropwise to the reaction solution, react for 2 hours, and then cool to room temperature to obtain an aqueous hollow elastic rubber microsphere modified silicone acrylic emulsion. The preparation method of the hollow elastic nano rubber microsphere is as follows: 75g of hollow glass microspheres with a particle size of 20 microns, 380g of vulcanized rubber elastic powder with a particle size of 15 microns, 1.2g of dodecyl dimethyl benzyl ammonium chloride, and 0.8g of γ-aminopropyl triethoxysilane are placed in 150g of ethylene glycol butyl ether solvent, heated and refluxed at 150°C for 20 minutes, cooled and filtered, and the filtrate is placed in a 60°C oven for 24 hours to obtain hollow elastic nano rubber microspheres.
[0032] Preparation Example 2 Preparation of modified hollow glass microspheres The method for preparing the modified hollow glass microspheres comprises the following steps: S41, soaking 200 g of hollow glass microspheres with a particle size of 20 μm in 2 L of 15% vinyltrimethoxysilane modified treatment solution and stirring for 30 minutes, filtering and drying to obtain an intermediate material; S42, add 100g of the intermediate material and 500mL of xylene into the reactor and mix evenly, then add 290g of phenylindanedione and 125g of methyl 4-benzoylbutyrate, then add 3g of sodium methoxide under constant stirring and react at 40°C for 7h, and after reduced pressure distillation, washing and drying, the modified hollow glass microspheres are obtained.
[0033] Preparation Example 3 Preparation of Nano-TiO2 Modified Aerogel Dispersion The method for preparing the nano-TiO2 modified aerogel dispersion comprises the following steps: S51, according to the mass parts, add 100 parts of TiO2 powder with a particle size of 20 nanometers and 15 parts of Tego760W, a wetting and dispersing agent, to 50 parts of deionized water, and disperse for 5 minutes at a dispersion speed of 400 r / min to obtain a solution A; S52, according to the mass fractions, add 15 parts of fumed silica gel and 2 parts of hydroxyethyl cellulose to 50 parts of deionized water, then add 0.5 parts of γ-aminopropyltriethoxysilane, and disperse for 10 minutes at a dispersion speed of 600 r / min to obtain a solution B; S53, adding solution B into solution A, dispersing for 20 minutes at a dispersing speed of 800 r / min, to obtain a nano-TiO2 modified fumed silica gel dispersion.
[0034] Example 1 A water-based heat-insulating material containing rare earth elements, comprising the following raw materials by weight: 50 parts of water-based hollow elastic rubber microsphere modified silicone acrylic emulsion, 12 parts of modified hollow glass microspheres, 7 parts of rare earth nano heat-insulating agent, 12 parts of nano TiO2 modified aerogel dispersion, 6 parts of kaolin, 0.5 parts of hydroxypropyl methylcellulose, 0.5 parts of dispersant, 1.5 parts of propylene glycol methyl ether acetate, 1.4 parts of dimethyl silicone oil, and 10 parts of deionized water, wherein the rare earth nano heat-insulating agent is an aqueous dispersion slurry of cerium-based rare earth oxides, and the dispersant is prepared by mixing BYK-190, sodium dodecyl phosphate, and sodium dodecylbenzene sulfonate in a weight ratio of 3:4:3; The method for preparing the above-mentioned water-based thermal insulation material containing rare earth elements comprises the following steps: S101, respectively adding water-based hollow elastic rubber microsphere modified silicone acrylic emulsion, modified hollow glass microspheres, rare earth nano thermal insulation agent, nano-TiO2 modified aerogel dispersion, kaolin, and deionized water into a reactor according to their mass fractions, and stirring at a speed of 300 r / min for 40 min to obtain a mixed solution; S102. Add hydroxypropyl methylcellulose, dispersant, propylene glycol methyl ether acetate and dimethyl silicone oil to the mixed liquid according to their mass proportions, and stir at a speed of 1200 r / min for 30 min to obtain a water-based thermal insulation material containing rare earth elements.
[0035] Example 2 A water-based heat-insulating material containing rare earth elements, comprising the following raw materials by weight: 55 parts of water-based hollow elastic rubber microsphere modified silicone acrylic emulsion, 15 parts of modified hollow glass microspheres, 9 parts of rare earth nano heat-insulating agent, 14 parts of nano TiO2 modified aerogel dispersion, 8 parts of kaolin, 0.8 parts of hydroxypropyl methylcellulose, 0.7 parts of dispersant, 2 parts of propylene glycol methyl ether acetate, 1.6 parts of dimethyl silicone oil, and 12 parts of deionized water, wherein the rare earth nano heat-insulating agent is an aqueous dispersion slurry of cerium-based rare earth oxides, and the dispersant is prepared by mixing BYK-190, sodium dodecyl phosphate, and sodium dodecylbenzene sulfonate in a weight ratio of 3:4:3; The method for preparing the above-mentioned water-based thermal insulation material containing rare earth elements comprises the following steps: S101, respectively adding water-based hollow elastic rubber microsphere modified silicone acrylic emulsion, modified hollow glass microspheres, rare earth nano thermal insulation agent, nano-TiO2 modified aerogel dispersion, kaolin, and deionized water into a reactor according to their mass fractions, and stirring at a speed of 300 r / min for 40 min to obtain a mixed solution; S102. Add hydroxypropyl methylcellulose, dispersant, propylene glycol methyl ether acetate and dimethyl silicone oil to the mixed liquid according to their mass proportions, and stir at a speed of 1200 r / min for 30 min to obtain a water-based thermal insulation material containing rare earth elements.
[0036] Example 3 A water-based heat-insulating material containing rare earth elements, comprising the following raw materials by weight: 53 parts of water-based hollow elastic rubber microsphere modified silicone acrylic emulsion, 14 parts of modified hollow glass microspheres, 8 parts of rare earth nano heat-insulating agent, 13 parts of nano TiO2 modified aerogel dispersion, 7 parts of kaolin, 0.7 parts of hydroxypropyl methylcellulose, 0.6 parts of dispersant, 1.7 parts of propylene glycol methyl ether acetate, 1.5 parts of dimethyl silicone oil, and 11 parts of deionized water, wherein the rare earth nano heat-insulating agent is an aqueous dispersion slurry of cerium-based rare earth oxides, and the dispersant is prepared by mixing BYK-190, sodium dodecyl phosphate, and sodium dodecylbenzene sulfonate in a weight ratio of 3:4:3; The method for preparing the above-mentioned water-based thermal insulation material containing rare earth elements comprises the following steps: S101, respectively adding water-based hollow elastic rubber microsphere modified silicone acrylic emulsion, modified hollow glass microspheres, rare earth nano thermal insulation agent, nano-TiO2 modified aerogel dispersion, kaolin, and deionized water into a reactor according to their mass fractions, and stirring at a speed of 300 r / min for 40 min to obtain a mixed solution; S102. Add hydroxypropyl methylcellulose, dispersant, propylene glycol methyl ether acetate and dimethyl silicone oil to the mixed liquid according to their mass proportions, and stir at a speed of 1200 r / min for 30 min to obtain a water-based thermal insulation material containing rare earth elements.
[0037] Comparative Example 1 The same as Example 3, except that the modified hollow glass microspheres are 27 parts and the nano-TiO2 modified aerogel dispersion is 0 parts.
[0038] Comparative Example 2 The same as Example 3, except that 0 parts of modified hollow glass microspheres and 27 parts of nano-TiO2 modified aerogel dispersion were used.
[0039] Comparative Example 3 The same as Example 3, except that an equal amount of hollow glass microspheres with a particle size of 20 μm are used instead of the modified hollow glass microspheres.
[0040] Comparative Example 4 The same as Example 3, except that the added amount of rare earth nano thermal insulation agent is 0 parts.
[0041] Comparative Example 5 The same as Example 3, except that the dispersant is BYK-190.
[0042] Comparative Example 6 The same as Example 3, except that the dispersant is sodium dodecyl phosphate.
[0043] Comparative Example 7 The same as Example 3, except that the dispersant is sodium dodecylbenzene sulfonate.
[0044] Performance Testing The water-based thermal insulation materials containing rare earth elements prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were sampled and coated. The coating dry film thickness was 220 μm. After coating, the coating was naturally dried and the following performance tests were performed. The test results are shown in Table 1. Adhesion (pull-off method): Tested in accordance with GB / T 5210; Thermal insulation temperature difference: tested in accordance with HG / T 5182, where the thickness of the coating applied to the sample is 1.5 mm; Thermal conductivity: Tested according to HG / T 5182; Alkali resistance: measured in accordance with the provisions of GB / T9274, using a mass concentration of 5% NaOH; Acid resistance: Determined in accordance with the provisions of GB / T9274, using 5% sulfuric acid; Salt spray resistance: measured in accordance with the provisions of GB / T1771; Water resistance: measured in accordance with the provisions of GB / T 1733; Anti-ultraviolet aging: Tested with reference to "GB / T 1865-2009 Paints and varnishes - Artificial weathering and artificial radiation exposure - filtered xenon arc radiation", with an irradiation time of 1000h.
[0045] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The water-based thermal insulation material containing rare earth elements obtained in Examples 1 to 3 has excellent adhesion, good thermal insulation effect, extremely low thermal conductivity and excellent thermal insulation temperature difference; it has excellent corrosion resistance and water resistance, and good aging resistance.
[0046] 2) The comparative analysis of the performance of the water-based thermal insulation materials containing rare earth elements prepared in combination with Example 3 and Comparative Examples 1-2 shows that the prepared modified hollow glass microspheres and the nano-TiO2 modified aerogel act synergistically, and the modified hollow glass microspheres can enhance the stability of the coating system, and have good anti-corrosion and water resistance, and good aging resistance.
[0047] 3) The performance comparison analysis of the water-based thermal insulation materials containing rare earth elements prepared in combination with Example 3 and Comparative Example 3 shows that the modified hollow glass microspheres react phenylindanedione and 4-benzoylbutyrate with vinyltrimethoxysilane in the intermediate material through a chemical reaction to form hollow glass microspheres with modified functions. The surface properties of the prepared modified hollow glass microspheres are improved, so that they can be better combined with the emulsion base material and dispersed. The role of the modified hollow glass microspheres in water-based thermal insulation materials is to reduce the thermal conductivity, improve the thermal insulation performance of the coating, and reduce the transfer of heat.
[0048] 4) The comparative analysis of the performance of the water-based thermal insulation materials containing rare earth elements prepared in Example 3 and Comparative Example 4 shows that the rare earth nano thermal insulation agent has good transparency and does not affect the light transmittance and color of the coating. 3+ and Ce4+ The reversible transformation between oxidation states, the resulting electronic resonance and energy level transition, greatly improve the thermal insulation performance of the coating. 3+ and Ce 4+ The reversible transformation process between oxidation states has a certain effect on the absorption of ultraviolet rays, and therefore significantly improves the anti-ultraviolet aging performance of the coating.
[0049] 5) The performance comparison analysis of the water-based thermal insulation materials containing rare earth elements prepared in combination with Example 3 and Comparative Examples 5-7 shows that the dispersant is prepared by mixing BYK-190, sodium dodecyl phosphate, and sodium dodecylbenzene sulfonate in a mass ratio of 3:4:3. The role of the dispersant is to help the solid particles in the coating (such as modified hollow glass microspheres, rare earth nano thermal insulation agents, etc.) to be uniformly dispersed in the liquid medium (aqueous emulsion) to prevent particle aggregation and sedimentation, thereby ensuring the uniformity and stability of the coating. The synergistic effect of these three dispersants is that different dispersants have different molecular structures and properties, and their combination can provide a more comprehensive dispersion effect to adapt to different types of solid particles. This may be because their interaction at the interface enhances the stable dispersion of solid particles. Through reasonable proportioning, the good dispersion of each component in the coating is ensured, thereby improving the overall performance of the coating, including adhesion, thermal insulation effect, water resistance, corrosion resistance, and aging resistance.
[0050] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. A water-based thermal insulation material containing rare earth elements, characterized in that: The preparation raw materials include the following by weight: 50-55 parts of aqueous hollow elastic rubber microsphere modified silicone acrylic emulsion, 12-15 parts of modified hollow glass microspheres, 7-9 parts of rare earth nano thermal insulation agent, 12-14 parts of nano TiO2 modified aerogel dispersion, 6-8 parts of kaolin, 0.5-0.8 parts of thickener, 0.5-0.7 parts of dispersant, 1.5-2 parts of film former, 1.4-1.6 parts of defoamer and 10-12 parts of deionized water, wherein the rare earth nano thermal insulation agent is an aqueous dispersion slurry of cerium-based rare earth oxides.
2. The water-based thermal insulation material containing rare earth elements according to claim 1, characterized in that: The preparation method of the aqueous hollow elastic rubber microsphere modified silicone acrylic emulsion comprises the following steps: S21, according to the mass fraction, add 4 parts of sodium dodecyl phosphate to 100 parts of deionized water, stir evenly, add 12 parts of hollow elastic nano rubber microspheres, stir at a speed of 500 r / min for 30 min, and obtain a dispersion; S22, adding 30 parts of butyl methacrylate, 13 parts of hexamethylcyclotetrasiloxane, 3 parts of potassium persulfate and 15 parts of 25% ammonia water to the dispersion according to their mass fractions, introducing nitrogen gas while stirring for 20 minutes, then heating to 83° C. and keeping the temperature for 40 minutes to obtain a reaction solution; S23. Add 25 parts of ethyl acrylate, 40 parts of vinyltrimethoxysilane and 10 parts of 30% potassium persulfate aqueous solution into the reaction solution according to their mass fractions. After reacting for 2 hours, cool to room temperature to obtain an aqueous hollow elastic rubber microsphere modified silicone acrylic emulsion.
3. The water-based thermal insulation material containing rare earth elements according to claim 2, characterized in that: The preparation method of the hollow elastic nano rubber microspheres is as follows: 75g of hollow glass microspheres with a particle size of 20 microns, 380g of vulcanized rubber elastic powder with a particle size of 15 microns, 1.2g of dodecyl dimethyl benzyl ammonium chloride, and 0.8g of γ-aminopropyl triethoxysilane are placed in 150g of ethylene glycol butyl ether solvent, heated under reflux at 150°C for 20min, cooled and filtered, and the filtrate is placed in an oven at 60°C and baked for 24h to obtain the hollow elastic nano rubber microspheres.
4. The water-based thermal insulation material containing rare earth elements according to claim 1, characterized in that: The preparation method of the modified hollow glass microspheres comprises the following steps: S41, soaking 200 g of hollow glass microspheres with a particle size of 20 μm in 2 L of 15% vinyltrimethoxysilane modified treatment solution and stirring for 30 minutes, filtering and drying to obtain an intermediate material; S42, add 100g of the intermediate material and 500mL of xylene into the reactor and mix evenly, then add 290g of phenylindanedione and 125g of methyl 4-benzoylbutyrate, then add 3g of sodium methoxide under constant stirring and react at 40°C for 7h, and after reduced pressure distillation, washing and drying, the modified hollow glass microspheres are obtained.
5. The water-based thermal insulation material containing rare earth elements according to claim 1, characterized in that: The method for preparing the nano-TiO2 modified aerogel dispersion comprises the following steps: S51, according to the mass parts, add 100 parts of TiO2 powder with a particle size of 20 nanometers and 15 parts of Tego760W, a wetting and dispersing agent, to 50 parts of deionized water, and disperse for 5 minutes at a dispersion speed of 400 r / min to obtain a solution A; S52, according to the mass fractions, add 15 parts of fumed silica gel and 2 parts of hydroxyethyl cellulose to 50 parts of deionized water, then add 0.5 parts of γ-aminopropyltriethoxysilane, and disperse for 10 minutes at a dispersion speed of 600 r / min to obtain a solution B; S53, adding solution B into solution A, dispersing for 20 minutes at a dispersing speed of 800 r / min, to obtain a nano-TiO2 modified fumed silica gel dispersion.
6. The water-based thermal insulation material containing rare earth elements according to claim 1, characterized in that: The thickener is hydroxypropyl methylcellulose.
7. The water-based thermal insulation material containing rare earth elements according to claim 1, characterized in that: The dispersant is prepared by mixing BYK-190, sodium dodecyl phosphate and sodium dodecylbenzene sulfonate in a mass ratio of 3:4:
3.
8. The water-based thermal insulation material containing rare earth elements according to claim 1, characterized in that: The film-forming agent is propylene glycol methyl ether acetate.
9. The water-based thermal insulation material containing rare earth elements according to claim 1, characterized in that: The defoaming agent is dimethyl silicone oil.
10. The water-based thermal insulation material containing rare earth elements according to claim 1, characterized in that: The method for preparing the water-based thermal insulation material containing rare earth elements comprises the following steps: S101, respectively adding water-based hollow elastic rubber microsphere modified silicone acrylic emulsion, modified hollow glass microspheres, rare earth nano thermal insulation agent, nano-TiO2 modified aerogel dispersion, kaolin, and deionized water into a reactor according to their mass fractions, and stirring at a speed of 300 r / min for 40 min to obtain a mixed solution; S102. Add thickener, dispersant, film-forming agent and defoaming agent to the mixed solution according to their mass fractions, stir at a speed of 1200 r / min for 30 min, and obtain a water-based thermal insulation material containing rare earth elements.
Citation Information
Cited By
Reflective thermal insulation coating and preparation method thereof, and coating and preparation method thereof
CN121851815A
